Estudo da atividade física diária e rigidez arterial em idosos normotensos - Lacerda, Gabriela Nolasco (2019)
Introduction: Aging is characterized by a loss of elasticity in the large arterial vessels, with a consequent increase in arterial stiffness and the development of cardiovascular diseases. Objective: The objective of this study was to verify the level of daily physical activity (DPA) and the corresponding arterial vascular stiffness in elderly individuals considered normotensive, in whom the effects of arterial hypertension would not be obviously observed. Methods: A total of 49 normotensive elderly individuals were selected from the Study of the Pulse Wave Velocity in the Elderly in an Urban Area in Brazil (Estudo da Velocidade da Onda de Pulso em Idosos em Área Urbana no Brasil; EVOPIU) database. Two questionnaires were used to evaluate the level of DPA and functional capacity of the elderly individuals. The individuals were separated according to pulse wave velocity (c-fPWV) tertile. The International Physical Activity Questionnaire (IPAQ) short form was used to evaluate the level of DPA, and the Health Assessment Questionnaire (HAQ) was used to assess functional capacity. Results: The DPA of the elderly subjects in the highest c-fPWV tertile was not different from that of subjects in the lower tertiles. For different levels of DPA, the c-fPWV values were similar. Regarding functional capacity, we observed that the subjects had little or no functional limitation. Conclusion: The present study shows that arterial stiffness in normotensive elderly individuals is present, and this seems to depend not on physical activity but on the aging state of arterial walls.